An axial flux permanent magnet synchronous generator for a gearless wind energy system - Ferreira, Ângela P. (2007)
In low speed applications such as wind energy conversion systems, the use of direct driven generators, instead of geared machines, reduces the number of drive components, which offers the opportunity to reduce costs and increases system reliability and efficiency. The Axial Flux Permanent Magnet (AFPM) generator is particularly suited for such application, since it can be designed with a large pole number and a high torque density. This paper presents the design, construction and experimental validation of a double-sided AFPM synchronous generator prototype, with internal rotor and slotted stators. Design objectives embrace achieving a good compromise between performance characteristics and feasibility of construction, which results in a cost competitive machine.